Impaired eating‐related quality of life in chronic rhinosinusitis. Issue 3 (28th November 2018) - Rowan, Nicholas R.; Soler, Zachary M.; Storck, Kristina A.; Othieno, Florence; Ganjaei, Kimia G.; Smith, Timothy L.; Schlosser, Rodney J.
Abstract : Background: Despite the tremendous burden of smell and taste dysfunction in patients with chronic rhinosinusitis (CRS), objective measures of smell and taste fail to fully account for eating‐related disruptions in CRS patient quality of life (QOL). In this study we sought to investigate the driving force behind impaired eating‐related QOL in CRS patients. Methods: Adult CRS patients were prospectively enrolled and answered a series of surveys relating to smell, taste, overall sinus‐specific QOL, and depression. Patients with both smell‐related and taste‐related eating complaints were considered to have impaired eating‐related QOL. Clinical demographics, objective chemosensory scores, and endoscopy scores were collected. Results: Seventy patients were enrolled and 23% showed impaired eating‐related QOL. In multivariable analyses, patients with aspirin‐exacerbated respiratory disease (AERD) showed 10.7 times higher odds of impaired eating‐related QOL (odds ratio [OR] 10.72; 95% confidence interval [CI], 1.09 to 105.09; p = 0.042); meanwhile, for every 1‐point increase in depression scores, the odds of impaired eating‐related QOL increased by 1.3 (OR 1.31; 95% CI, 1.10 to 1.57; p = 0.003). For every 1‐point decrease in orthonasal olfactory threshold, the odds of impaired eating‐related QOL increased by 1.9 times (OR 1.85; 95% CI, 1.14 to 3.00; p = 0.013). Symptom scores, polyp status, endoscopic scores, and other olfactory measures did not remain significant after adjusting for other variables in forward‐selection multivariable modeling. Conclusion: Disruptions in eating‐related QOL cannot be fully explained by objective smell or taste testing alone. We identified AERD and depression as independent risk factors for greater odds of impaired eating‐related QOL in CRS. Improved orthonasal threshold scores were independently associated with better eating‐related QOL.